2019
DOI: 10.3390/ani10010017
|View full text |Cite
|
Sign up to set email alerts
|

Early Parenteral Administration of Ceftiofur has Gender-Specific Short- and Long-Term Effects on the Fecal Microbiota and Growth in Pigs from the Suckling to Growing Phase

Abstract: Simple Summary: Antibiotics are commonly used in prevention and therapy of bacterial diseases in pig production. Although the main target of antibiotics are the pathogenic bacteria, they often disrupt the commensal gut microbiota as a whole, leading to intestinal disturbances. These detrimental effects have been well established for oral administration of antibiotics, whereas knowledge about potential disturbing effects of single parenteral antibiotic treatments on the gut microbiota development is limited. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…However, the latter study did not investigate how quickly the differences became established. More recently, Ruczizka, et al [38] observed differences in the microbiota of piglets given a single intramuscular injection of ceftiofur 12 h post-partum, with differences evident at 12, 28 and 97 days of age. This approach was conducted in a more similar manner to the one implemented in the current study, therefore, it is likely that our inability to detect an effect of antibiotic may be due to a need for a longer period of time after antibiotic administration in order to see a change in the faeces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the latter study did not investigate how quickly the differences became established. More recently, Ruczizka, et al [38] observed differences in the microbiota of piglets given a single intramuscular injection of ceftiofur 12 h post-partum, with differences evident at 12, 28 and 97 days of age. This approach was conducted in a more similar manner to the one implemented in the current study, therefore, it is likely that our inability to detect an effect of antibiotic may be due to a need for a longer period of time after antibiotic administration in order to see a change in the faeces.…”
Section: Discussionmentioning
confidence: 99%
“…This approach was conducted in a more similar manner to the one implemented in the current study, therefore, it is likely that our inability to detect an effect of antibiotic may be due to a need for a longer period of time after antibiotic administration in order to see a change in the faeces. Additionally, Ruczizka, et al [38], also observed sex-specific differences and had 16 piglets of each sex per treatment. So, the lower number of replicates in the present study may have impacted the results.…”
Section: Discussionmentioning
confidence: 99%
“…This also suggests that, for the development of new products that promote the nutrition of the suckling or weaning pig, a complex pattern of sugars should be considered instead of a single one. OS continue to be produced in transitional and mature pig milk, and, hence, it can be assumed that these OS also modulate the establishment of the microbiota in piglets' intestine [9] which is known to mature with age [34,35] and influence the piglets' growth [36][37][38]. Though the OS composition in transitional and mature milk was not analysed in this study, the obtained results could imply that OS composition can contribute to the programmed development of the gut microbiota, since different OS clusters were associated with different final weaned litter weights and different average piglet growth during the first 3 days of life (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota of the GIT plays an important role in processing signals and cues from the environment and delivering them to the host ( Celi et al., 2019 ; Dietert and Silbergeld, 2015 ). However, a number of factors influence the diversity and activity of the intestinal microbiota, such as colonization and associated succession of inhabitation, dietary composition, feeding methods, feed processing, feed additives, antimicrobial agents, disease load, season, environment, stress, and genetics ( Guevarra et al., 2019 ; Ji et al., 2019 ; Rinninella et al., 2019 ; Ruczizka et al., 2019 ). Furthermore, the gut microbiota displays a compromise between supportive barrier functionality, synthesis of beneficial nutrients and proteins, and improved energy accumulation from diets, and the deleterious effects of inflammatory and clinical or subclinical pathologies ( Celi et al., 2017 ; Pluske et al., 2018 ).…”
Section: Prebiotics and Intestinal Microbiota Modulation Of Monogastrmentioning
confidence: 99%